(3GdTGFYGJ hTHcGJ GdJhGUd GdGLJeGYj (B:s (3GdeNGWQ hSHd GdehGLgI (B/s - (3GdYRYRj, hOjY eMeO SYjOs ((3YeGf, GdCQOf (B:s (3OGQ GdMGeO ddfTQ hGdJhRjY,s, 2019)
(3jhRY GdcJGH Ydi CQHYI aUhd jSJYQV GdaUd GdChd (B%22(3eGgjI GdTGFYGJ hCgOGagG hNUGFgG hCfhGYgG heQGMd JchjfgG hYhGed GfJTGQgG(B%22 (3hjJfGhd GdaUd GdKGfj (B%22(3THcGJ GdJhGUd GdGLJeGYj eaghegG heejRGJgG hCfhGYgG h JCKjQGJgG(B%22 (3ajeG jfGbT GdaUd GdKGdK (B%22(3hGbY GdTGFYGJ aj THcGJ GdJhGUd GdGLJeGYj hYdGbI ehGbY GdJhGUd GdGLJeGYj HGdTGFYGJ hOhQ THcGJ GdJhGUd GdGLJeGYj aj fTQ GdTGFYGJ hBdjGJ fTQgG heUGOQgG HGdEVGaI Gdi ghjI GdaQO aj THcGJ GdJhGUd GdGLJeGYj(B%22 (3hJfGhd GdaUd GdQGHY (B%22(3eNGWQ GdTGFYGJ hSHd GdehGLgI(B.s
(3HHdjhLQGajI (B: (3UaMI (B117-127.s
Keywords: (3GdTHcGJ GdGLJeGYjI Ydi GdEfJQfJs -- (3LhGfH GLJeGYjIs; (3GdETGYGJs -- (3LhGfH GLJeGYjIs